Implementasi Santunan Anak Yatim Di Kelurahan Tamansari Dalam Memperingati Tahun Baru Islam - Asih Setyo Rini; Febry Aurora Galla; Mochamad Farel Akbar; Sulis Setya Damayanti; Sinta Purnamasari; Hida Nurhekmy; Muhamad Ari Yanuar; Yulianti Yulianti; Hadi Nur Amanah; Ajeng Dwi Pangestika Indrageni; Marini Marini; Winda Safitri; Muhammad Faiz Muzaqi Suparman; Asep Eka Mulyanudin; Ahmad Sayuri; Suherni Suherni; Sofiya Ulfa (Universitas Maritim AMNI Semarang, 2023)
One part of the tridharma of higher education is community service. One example of community service activities is Student Work Lectures or KKM. In KKM activities, there are several work programs that must be carried out and divided into each sector. Like the religious sector, in realizing the work program in the religious sector, KKM Group 72 UNIBA held an open donation activity for compensation for orphans at Link. Sumur Jaya RT/RW 04/02 Tamansari Village. After the donations were collected, they were then handed over to the local Risma administrators to be given to them. to orphans.